An analysis study on role of chaos in symmetric encryption algorithm - Özkaynak, Fatih; Özer, Ahmet Bedri (ISAST: International Society for the Advancement of Science and Technology, 2015)
In this study, we examine randomness properties of chaos based cryptographic designs. The analysis studies show that chaotic outputs which are used as a source of randomness, successfully pass the standard statistical tests, but their cryptographic randomness properties are worse than any standard random function. With these results, suitability of digital chaos in new cryptologic designs should be re-evaluated by the chaotic cryptology literature. © 2015 ISAST.
8th International Conference on Chaotic Modeling and Simulation, CHAOS 2015 -- 26 May 2015 through 29 May 2015 -- Paris -- 151087
Keywords: Chaos; Cryptographically randomness; Cryptography; Digital chaos; Effect of computation precision